FOREWORD - Dimova, Violeta (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
As I am writing the foreword for “Palimpsest” I feel tremendous pleasure,but also a need to express the reasons for establishing this journal precisely underthis name. Today, in the era of information technology with the option for electronicpublications, the name of our international scientific journal “Palimpsest”(παλίμψηστος / palimpsestos or Codex rescriptus meaning “re-scripted or scrapedagain”, “obtained again”) - a word that in its essence refers to a manuscript, aparchment from which the text has been removed or washed to be used again forrewriting – expresses our commitment to respect previous experiences and on thatbasis to build new ones.The first issue of “Palimpsest”, which is an international scientific journalfor linguistic, literary and cultural studies, is published exactly eight years after theestablishment of the Faculty of Philology at Goce Delcev University in Stip. Thisis just another confirmation that the Faculty seriously and firmly stands on the pathof strengthening the scientific and research activities in the field of humanities asa result of the commitment and perseverance of the academic staff. During itseight years of existence as part of the academic community, we can certainlysay that as a relatively young faculty we have managed to lay solid foundationsupon which we build and upgrade our knowledge and experience, both in thefield of linguistics and literary science, as well as in the improvement of teachingmethodology and cultural studies, which can be confirmed with the papers thatare publish the first issue of “Palimpsest” whose authors are part of the academicstaff of this faculty and can confirm their research potential in this way as well.To our great pleasure, the content of “Palimpsest” is enriched with papersby well-known scholars from the country and abroad, which encourages us tocontinue with the publication of this journal and thus to establish importantrelations in the fields of language, literature and culture in our country and abroad.Finally, I wish the Editorial Board a great and continuing success in thefuture with the sincere belief that the international scientific journal “Palimpsest”will justify its name and will be the “parchment” on which the new generations ofscientists will leave their trace.